K-pop music: the influence of pop-culture involvement and destination image on travel intention to south korea - Putong, Paulina Elizabeth; Dermawan, Stefany; Thio, Sienny (Institut Pariwisata dan Bisnis Internasional, 2022)
This study implements the concept of pop-culture involvement, specifically K-Pop music. Pop-culture involvement is classified into two categories, situational involvement, and enduring involvement. This study aims to investigate the involvement of pop-culture in shaping a destination image that will influence the intention to travel. A quantitative study by distributing questionnaires was performed on 135 Indonesian citizens aged 17 and above. The Partial Least Square (PLS) method was employed to process the data acquired. The result indicates that situational involvement has a significant influence in forming enduring involvement. Situational involvement also influences the destination image, yet enduring involvement has no effect on destination image. In addition, the result also shows that destination image does significantly affect travel intention. This study has provided a preliminary investigation on pop-culture involvement of K-Pop music. It is expected to be insights for further research specifically in the context of K-Pop music and tourism.